PERANCANGAN GAME EDUKASI ILMU PENGETAHUAN ALAM DAN ILMU PENGETAHUAN SOSIAL BERBASIS ANDROID (STUDI KASUS SMAN 4 JAMBI) - Maryandi Maryandi; Erick Fernando; M. Riza Pahlevi B (LPPM STIKOM Dinamika Bangsa, 2014)
This study discusses the design of educational games Natural Sciences and Social Sciences based on android (4 Jambi SMAN case study). Based on the results of the identification of the existing problems in SMAN 4 Jambi, students are still having trouble receiving a lesson in school. This is due to the lack of time when the teacher explains the subject matter and a question and answer between teachers and students in school. For research and development in the design of educational game is conducted by four stages, namely planning, system design, system design and development. Of the four stages of this one is the design process can be done by analyzing the concept of the material about to be shown, by creating a class diagram. And for development system to use the system waterfall (waterfall). The objectives to be achieved in this research is to support the memory of students in the learning process and help students in getting additional material from educational games he played. This educational game in the form of a quiz game that can be played by students from class X, XI, and XII with a single player. Problems and their levels can also be added and deleted as desired admin / teacher school SMAN 4 Jambi. This educational game can be played on Android smartphones with version 2.3 of the Android Gingerbread minimum and maximum android smartphone is Android 5.0 Lollipop. Keywords : Game Design education, Natural Sciences and Social Sciences, Android.